Law & ethics for medical careers - Judson, Karen 1941- (McGraw-Hill Higher Education, 2010)
Introduction to law and ethics -- Working in health care -- Law, the courts, and contracts -- Professional liability and medical malpractice -- Defenses to liability suits -- Medical records and informed consent -- Privacy law and HIPAA -- Physicians' public duties and responsibilities -- Workplace legalities -- The beginning of life and childhood -- Death and dying -- Health care trends and forecasts.